2005
DOI: 10.1128/cdli.12.1.141-151.2005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Several Serological Tests and Antigens for Diagnosis of Bovine Brucellosis in the Presence of False-Positive Serological Results Due to Yersinia enterocolitica O:9

Abstract: Brucellosis is a disease caused by members of the genus Brucella that affects animals and humans. The species that infects cattle most often is Brucella abortus, but cattle infections by Brucella melitensis are not rare in areas where there is contact with infected sheep and goats (63, 64). Both B. abortus and B. melitensis are termed smooth (S) because they bear a S-type lipopolysaccharide (S-LPS). Many serological tests have been proposed for the diagnosis of brucellosis caused by S brucellae, and they can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
107
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(122 citation statements)
references
References 48 publications
1
107
1
5
Order By: Relevance
“…and the above mentioned bacteria (Hinić et al, 2009). False positive serological results are due only to Y. enterocolitica O: 9 affect up to 15% of the cattle herds in regions free from brucellosis, generating considerable additional costs for surveillance programs (Muñoz et al, 2005). False negative results have also been observed in serological diagnosis of brucellosis (Godfroid et al, 2002;Tessaro and Forbes, 2004).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…and the above mentioned bacteria (Hinić et al, 2009). False positive serological results are due only to Y. enterocolitica O: 9 affect up to 15% of the cattle herds in regions free from brucellosis, generating considerable additional costs for surveillance programs (Muñoz et al, 2005). False negative results have also been observed in serological diagnosis of brucellosis (Godfroid et al, 2002;Tessaro and Forbes, 2004).…”
Section: Introductionmentioning
confidence: 94%
“…However, cross-reactions between Brucella species and other Gram-negative bacteria, such as Yersinia enterocolitica O:9, Francisella tularensis, Escherichia coli O:157, Salmonella urbana group N, Vibrio cholerae and Stenotrophomonas maltophilia, are a major problem of the serological assays (Muñoz et al, 2005;Al Dahouk et al, 2006). The source of antigenic cross reactions is the O-chain of the smooth lipopolysaccharide (S-LPS) present on the surface of the bacterial cell, which shows great similarity in smooth Brucella spp.…”
Section: Introductionmentioning
confidence: 99%
“…This is accomplished by selecting a MAb that has higher affinity than cross-reacting antibody. However, it has been shown that the c-ELISA eliminates some but not all reactions due to cross-reacting bacteria (Munoz et al, 2005;Neilson, 2002).The c-ELISA is also capable of eliminating most reactions due to residual antibody produced in response to vaccination with S19. The choice of MAb and its unique specificity and affinity will have a distinct influence on the diagnostic performance characteristics of the assay.…”
Section: Study Areamentioning
confidence: 99%
“…The competitive ELISA (c-ELISA) using monoclonal antibody (MAb) specific for one of the epitopes of the Brucella sp. OPS has been shown to have higher specificity but lower sensitivity than the I-ELISA (Macmillan et al, 1990;Munoz et al, 2005;Neilson et al, 1995;Stuck et al, 1999 andWeynants et al, 1997). This is accomplished by selecting a MAb that has higher affinity than cross-reacting antibody.…”
Section: Study Areamentioning
confidence: 99%
“…This genetic similarity is known to cause crossreactivity between the two bacteria during serologic testing. As a result, infection with Y. enterocolitica serotype O:9 can lead to false-positive Brucella serology tests, making identification of Brucella-positive animals difficult in livestock and wildlife populations including cattle, bison, and elk (Weynants et al, 1996;Munoz et al, 2005;Atkinson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%